Réponses

2014-03-28T15:00:21+01:00
= (6x-7)(-3-2x)
A = 6x*(-3) + 6x*(-2x) -7*(-3) - 7*(-2x)
A = -18x-12x
²+21+14x
A = -12x²-4x+21

Pour x = 0 :

A = -12*(0)²-4*(0)+21
A = 21

Pour x = 1

A = -12*(1)²-4*(1)+21
A = -12*(1)-4+21
A = -12-4+21
A = 5
2014-03-28T15:04:54+01:00
1)Développer et réduire l expression:
A=(6x-7)(-3-2x)
A = -18x-12x
²+21+14x
A= -12x²-4x+21

2)Calculer A pour x =0, puis pour x=1
A(0) = -12*0-4*0+21
A(0) = 21

A(1) = -12*1-4*1+21
A(1) = -12-4+21
A(1) = 5

* = fois, pultiplié par